Maqashid Sharia Perspective on Judges' Considerations in Determining the Origin of Children - 'Afifa Zulkifli, Rizka; Bahar, Muchlis; Elfia, Elfia; Zulkifli, Zulkifli (UIN Mahmud Yunus Batusangkar, 2025)
This study aims to analyze the legal considerations of the Panel of Judges in granting the application for child origin at the Talu Religious Court in Determination Number 355/Pdt.P/2021/PA.Talu, and how these considerations are viewed from the maqashid sharia perspective. The research method used is normative juridical with a qualitative approach, where data is obtained through literature study and analyzed descriptively. The results showed that the Panel of Judges decided to accept/grant the petition after considering the evidence submitted, including testimonies and supporting documents regarding the applicants' siri marriage and household conditions. The decision was in accordance with maqashid sharia, which emphasizes the importance of preserving offspring (hifz al-nasl) and eliminating harms, especially in relation to obtaining legal documents to guarantee children's civil rights, such as nasab and inheritance rights.